NGOs dalam konteks dinamika rezim internasional = NGOs in the International Regime Dynamycs - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
International regime on aid and investment also have some negative impacts. This regime significantly based on the absortive capacity of capital tends to make developing countries, such as Indonesia, on the continually asymmetrical dependency. On the one hand it indicates the sensitivity of those countries, in which theoritically will be easeily intervened by outsiders, but on the other hand it gives opportunity for the governments to manipulate their sensitivity through what is commonly known as policies adjustment. Further implication of such regime is the decreasing of the economic, soclo-cultural and political rights of people as shown by Kedung Ombo Dam Project. How Non-Governmental Organizations (NGOs) take roles in this regime is the main concern of this thesis. From four models of explanation two are able to represent the NGOs'. movements. The issue structure explanation argues that in the "multiplechannels" and "the absence of hierarchy among issue" of interdependence the NGOs have chance to raise the negative impacts and make it as an international issue. Meanwhile, the international organization model provides the NGOs with bargaining politics as a process of influencing regime makers in order to include social, political and environmental requirements in any agreement dealing with transfer of international aid and investment.